Immune dysregulation and Th2 polarization are associated with atopic dermatitis in heart‐transplant children: A delicate balance between risk of rejection or atopic symptoms. Issue 5 (25th January 2019) - López‐Abente, Jacobo; Bernaldo‐de‐Quirós, Esther; Camino, Manuela; Gil, Nuria; Panadero, Esther; Campos‐Domínguez, Minia; Seoane‐Reula, Elena; Gil‐Jaurena, Juan M.; Pion, Marjorie; Correa‐Rocha, Rafael
Abstract : Atopic dermatitis (AD) has a high incidence in heart‐transplant children, and the reason why there is more AD after transplantation is still unknown. We conducted a cross‐sectional study comparing 11 AD and 11 non‐AD age‐matched heart‐transplant children, to assess which immune alterations are related to AD in these patients. AD patients had been transplanted at a younger age compared to non‐AD, indicating that age at transplant may be determinant in the onset of AD. The earlier thymectomy in AD heart‐transplant children favored the presence of more differentiated phenotypes in the T cell compartment. We observed a clear reduction in the T‐helper 1/T‐helper 2 (Th1/Th2) ratio in AD children. This Th2 polarization was related to eosinophilia and high immunoglobulin E levels, but also to an impaired regulatory T cell (Treg) suppression, which could be secondary to an exhaustion of the Treg compartment. Interestingly, AD patients were free of rejection episodes (0/11) in comparison to non‐AD children (4/11). We propose that a predominant Th2 phenotype may prevent the emergence of Th1 responses associated with graft rejection. A more differentiated Treg phenotype could also play a role in preventing acute rejection in the first year posttransplant. Our findings provide useful insights and knowledge for the better understanding of atopic disorders in transplanted children. Abstract : Younger age at transplantation and the subsequent thymectomy in children with heart transplants favors a Th2 polarization in the T cell compartment that could contribute to the onset of atopic dermatitis in these patients.